Biochemical Effects of Two Pesticides in Three Different Temperature Scenarios on the Diatom Thalassiosira weissflogii - Mesquita, Andreia F. (2021)
The exponential increase of the human population demands the overuse of fertilizers and pesticides in agriculture practices to suppress food production needs. The excessive use of these chemicals (fertilizers and pesticides) can comport deleterious effects to the ecosystems, including aquatic systems and communities. Oxyfluorfen is a fluorine-based herbicide, and its application has increased, since it is seen as an alternative to control glyphosate-resistant weeds. Copper sulfate is an inorganic pesticide based on copper which is being used in several chemical formulations, and it is the second main constituent of fungicides. Besides the known effects of such products in organisms, climatic changes pose an additional issue, being a main concern among scientists and politicians worldwide, since these alterations may worsen ecosystems’ and organisms’ sensitivity to stress conditions, such as the exposure to pollutants. Thalassiosira weissflogii (Grunow) G. A. Fryxell & Hasle, 1977 plays an important role in aquatic food webs as a primary producer and an essential food source to zooplankton. Thus, alterations on the diatom’s abundance and nutritional value may lead to consequences along the trophic chain. However, few studies have evaluated the biochemical impacts of oxyfluorfen and copper sulfate exposure on diatoms. This study intends to (1) evaluate the effects on the growth rate of both contaminants on T. weissfloggi at three temperatures, considering the actual scenario of climatic changes, and (2) assess biochemical changes on the diatom when exposed to the chemicals at different temperatures. To achieve these aims, the marine diatom was exposed to the two chemicals individually at different temperatures. The results showed an increase in the growth rate with increasing temperatures. Oxyfluorfen exhibited higher toxicity than copper sulfate. At the biochemical level, the microalgae were greatly affected when exposed to oxyfluorfen at 20 C and 25 C and when exposed to copper sulfate at 15 C. Moreover, a general increase was observed for the polysaccharide content along the copper sulfate and oxyfluorfen concentrations. Therefore, the contaminants show the ability to interfere with the diatom growth and the nutritive value, with their effects dependent on the temperature.